Study of Electrical and Mechanical Properties of Polyester and Graphene Composites - Ahmed J. Mohammed; Zainab J. Sweah; Ghufran.M. Shabeeb; Ibrahim Kadim A (Genius Journals, 2023)
The exotic physical properties of graphene have led to intense research activities on the synthesis and characterization of graphene during the last decade. In this article, the methods developed for the preparation of such materials and the different application areas are reviewed. The composites discussed are of two types, via; graphene/polymer. The weight percent of graphene was 1%, 3%, 5% and 7% wt percent of the total weight of polyester were investigated. Electrical and mechanical properties were also investigated for all prepared ratios
Keywords: Polyester; graphene; electrical properties